Wrist arthroscopy in the management of distal radius fractures - Shkolnikova, Julia; Harvey, Jason (Annals of Joint; Vol 3 (September 2018): Annals of Joint, 2018)
Wrist arthroscopy is a valuable tool in the management of distal radius fractures. It can assist with restoration of the articular surface and in identification of associated soft tissue injuries. It is important to recognize fractures that may benefit from the procedure and to be familiar with the technical aspects of performing wrist arthroscopy in the setting of fracture. This review details the advantages and disadvantages of wrist arthroscopy in the management of distal radius fractures and discusses the indications for the procedure, techniques and the outcome of treatment.